2020
DOI: 10.1097/rti.0000000000000515
|View full text |Cite
|
Sign up to set email alerts
|

Diffusely Increased Myocardial Extracellular Volume With or Without Focal Late Gadolinium Enhancement

Abstract: Cardiovascular disease contributes greatly to the disease burden in many developed countries. Cardiovascular magnetic resonance (CMR) is a powerful imaging modality that can diagnose a vast range of these diseases. When combined with an extracellular contrast agent, CMR can not only diagnose the function and size of the heart but also provide detailed information on the myocardial tissue. CMR T1 and extracellular volume (ECV) mapping can be used to quantitatively characterise the tissue properties of the myoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…This study was a retrospective analysis, and enrolled patients were not scanned for such new technologies. A recent article reported that ECV combined with LGE provided additional diagnosis and prognosis for LV dysfunction 26. Ideally the results with regard to sensitivity and specificity need validation in an independent patient cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was a retrospective analysis, and enrolled patients were not scanned for such new technologies. A recent article reported that ECV combined with LGE provided additional diagnosis and prognosis for LV dysfunction 26. Ideally the results with regard to sensitivity and specificity need validation in an independent patient cohort.…”
Section: Discussionmentioning
confidence: 99%
“…A recent article reported that ECV combined with LGE provided additional diagnosis and prognosis for LV dysfunction. 26 Ideally the results with regard to sensitivity and specificity need validation in an independent patient cohort. In view of the above 2 points, a prospective study would be necessary to confirm which etiology could mainly account for the LV dilation and dysfunction.…”
Section: Limitationsmentioning
confidence: 99%
“…5 Cardiovascular magnetic resonance (CMR) imaging is widely accepted as the modality of choice for the quantitative evaluation of the heart, and it is well suited to provide a detailed characterization of a wide variety of cardiomyopathies. [6][7][8][9][10][11] Nevertheless, assessing myocardial function in HCM by cardiac imaging is imprecise since standard functional parameters, such as LV ejection fraction (LVEF), are often preserved or supernormal in HCM patients despite clinical heart failure symptoms. Late gadolinium enhancement (LGE) of CMR is currently recognized as the gold standard for noninvasive evaluation of myocardial focal alternative fibrosis.…”
mentioning
confidence: 99%